Marx : the alternative to capitalism - Allen, Kieran, 1954- (Pluto Press, 2017)
An accessible and comprehensive overview of the ideas of Karl Marx that elucidates his theories and suggests crucial alternatives to capitalism.
Originally published in 2011 with title: Marx and the alternative to capitalism.
Keywords: Marx, Karl, -- 1818-1883 -- Political and social views.; Marx, Karl, -- 1818-1883; Communism.; Socialism.; POLITICAL SCIENCE -- Political Ideologies -- Communism & Socialism.; Communism; Political and social views; Socialism; Electronic book.